2001
DOI: 10.1254/jjp.87.110
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of FR183998, a Na+H+ Exchange Inhibitor, Against Postischemic Injury After Normothermic and Prolonged Hypothermic Ischemia in Isolated Perfused Rat Hearts

Abstract: ABSTRACT-Inhibition of Na+ / H + exchanger has been reported to protect hearts from ischemia and reperfusion injury. However, the effect of Na + /H + exchange inhibition on hypothermic ischemic injury has not been extensively studied and the results are inconsistent. The purpose of this study was to investigate whether inhibition of Na+ exchange inhibitor, would show protective effects against postischemic cardiac dysfunction after hypothermic as well as normothermic ischemia and furthermore, after hypothermic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…13,25,31 There are several diseases that may be associated with or induced by altered NHE activity, including hypertension, cardiac ischemia, and reperfusion injury. 2,7,9,29,35,36 An increased [Na ϩ ] i activates the Na ϩ /Ca ϩϩ exchanger and results in an increase in free [Ca ϩ ] i . 26 As expected, not only [Na ϩ ] i overload but also ischemic Ca ϩϩ overload is substantially reduced by Na ϩ /H ϩ exchange inhibitors.…”
Section: The Nhe In Pathological Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…13,25,31 There are several diseases that may be associated with or induced by altered NHE activity, including hypertension, cardiac ischemia, and reperfusion injury. 2,7,9,29,35,36 An increased [Na ϩ ] i activates the Na ϩ /Ca ϩϩ exchanger and results in an increase in free [Ca ϩ ] i . 26 As expected, not only [Na ϩ ] i overload but also ischemic Ca ϩϩ overload is substantially reduced by Na ϩ /H ϩ exchange inhibitors.…”
Section: The Nhe In Pathological Conditionsmentioning
confidence: 99%
“…3,25,31 It has been reported in preclinical studies that Na ϩ /H ϩ exchange inhibitors have cardioprotective effects. 2,7,9,29,35,36 Recently, it has been reported that inhibition of NHE by FR183998 may have beneficial effects in reducing infarct volume and brain edema during cerebral ischemia in rats. 17 Horikawa, et al, 11 reported that the protective effect of Na ϩ / H ϩ exchange inhibitor on ischemic brain injury in rats may be at least partially mediated by the prevention of endothelial dysfunction.…”
Section: The Nhe In Pathological Conditionsmentioning
confidence: 99%